Visualization of flow field and wake over clean and under-loaded wings - Al-Kayiem, H.H. (Trans Tech Publications Ltd, 2014)
Experimental details of the flow field and wake over airfoils and 2-D wings are time and cost consumption. In this study, the flow visualization technique was adopted to investigate the flow field surrounding NACA4412 airfoil. The investigations were carried out in smoke tunnel, operating at low Reynolds number in a range of 105. The airfoil was tested in two operational cases: first as clean wing and the second as under-loaded wing by attached missile model. The experiments were conducted at various angles of attack as 0°, 5°, 10°, 15° and 20°. It was found that the under-load of external body under the wing is influencing the flow structure over the wing. Also, the wake after the external body is swirling, leading to very complicated wake interaction. The results from the work can support the numerical simulation and the prediction of the laminar to turbulent transition and the separation and wake interaction of high lift airfoil flow fields. © (2014) Trans Tech Publications, Switzerland.